The time course of disuse muscle atrophy of the lower limb in health and disease. Issue 6 (14th September 2022) - Hardy, Edward J. O.; Inns, Thomas B.; Hatt, Jacob; Doleman, Brett; Bass, Joseph J.; Atherton, Philip J.; Lund, Jonathan N.; Phillips, Bethan E.
Abstract: Short, intermittent episodes of disuse muscle atrophy (DMA) may have negative impact on age related muscle loss. There is evidence of variability in rate of DMA between muscles and over the duration of immobilization. As yet, this is poorly characterized. This review aims to establish and compare the time‐course of DMA in immobilized human lower limb muscles in both healthy and critically ill individuals, exploring evidence for an acute phase of DMA and differential rates of atrophy between and muscle groups. MEDLINE, Embase, CINHAL and CENTRAL databases were searched from inception to April 2021 for any study of human lower limb immobilization reporting muscle volume, cross‐sectional area (CSA), architecture or lean leg mass over multiple post‐immobilization timepoints. Risk of bias was assessed using ROBINS‐I. Where possible meta‐analysis was performed using a DerSimonian and Laird random effects model with effect sizes reported as mean differences (MD) with 95% confidence intervals (95% CI) at various time‐points and a narrative review when meta‐analysis was not possible. Twenty‐nine studies were included, 12 in healthy volunteers (total n  = 140), 18 in patients on an Intensive Therapy Unit (ITU) (total n  = 516) and 3 in patients with ankle fracture (total n  = 39). The majority of included studies are at moderate risk of bias. Rate of quadriceps atrophy over the first 14 days was significantly greater in the ITU patients (MD −1.01 95% CI −1.32, −0.69), than healthy cohorts (MD −0.12 95% CI −0.49, 0.24) ( P  < 0.001). Rates of atrophy appeared to vary between muscle groups (greatest in triceps surae (−11.2% day 28), followed by quadriceps (−9.2% day 28), then hamstrings (−6.5% day 28), then foot dorsiflexors (−3.2% day 28)). Rates of atrophy appear to decrease over time in healthy quadriceps (−6.5% day 14 vs. −9.1% day 28) and triceps surae (−7.8% day 14 vs. −11.2% day 28), and ITU quadriceps (−13.2% day 7 vs. −28.2% day 14). There appears to be variability in the rate of DMA between muscle groups, and more rapid atrophy during the earliest period of immobilization, indicating different mechanisms being dominant at different timepoints. Rates of atrophy are greater amongst critically unwell patients. Overall evidence is limited, and existing data has wide variability in the measures reported. Further work is required to fully characterize the time course of DMA in both health and disease.